Prerequisites for economic development of territories taking account of ecological factors - Kupriyanchyk, I.; Kolisnyk, G. (Land Management, Cadastre and Land Monitoring, 2020)
The problem of the irrational use of the economic, land potential of the territories, the inefficient use of natural resources is considered, and the need for the integrated development of territories, the integral relationship of the regional economy and ecology, and rational nature management, especially in modern conditions, is substantiated. It has been determined that the policy of rational use of natural resources depends on the level of socio-economic development of the country and the change of indicators of the ecological and economic system should ensure preservation of the natural environment for the present and future generations. It is proved that for the effective functioning of the ecological and economic system it is necessary to take into account the influence of three main components: society, life, environment. It is indicated that the problem of improving the efficiency of the ecological and economic system is associated with the analysis of the impact of the economy on the environment and with the problems of choosing the optimal strategy and tactics in managing the economy of the region. To this end, a block diagram has been drawn up reflecting the necessary measures for the rational use of natural resources and environmental protection at the regional level and their content, as well as the directions of the regional environmental and economic policy, as the basis for sustainable development of the state, improving environmental safety and quality of life of the population. Keywords: economic development, environmental factors, ecological and economic systems, socio and economic development.